2021
DOI: 10.3390/vaccines9070695
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Healthcare Workers Vaccinated against Influenza in the Era of COVID-19

Abstract: Understanding the potential impact of COVID-19 on receiving influenza vaccination among healthcare workers (HCWs) is of utmost importance. The purposes of the present cross-sectional study were to describe the characteristics and to explore the predictors of receiving influenza vaccination among a large cohort of Italian HCWs in hospital settings. Information was collected through an anonymous questionnaire from December 2020 through January 2021. General and practice characteristics, perceived risk of seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
1
11
1
1
Order By: Relevance
“…Indeed, having received information about COVID-19 vaccination from scientific journals was one of the most significant influential factors of the self-reported reason that it was important to have this vaccination for fear of getting the disease. This is consistent with previous studies also conducted in other countries that have shown that having received information from the scientific journals had a positive influence on the individual decision making regarding vaccination [29,[34][35][36][37][38][39][40][41][42]. There is clearly a need for HCWs, as part of this sample, to be able to develop competencies aimed to overall improve the vaccination uptake for them and for the general population in this geographic area.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, having received information about COVID-19 vaccination from scientific journals was one of the most significant influential factors of the self-reported reason that it was important to have this vaccination for fear of getting the disease. This is consistent with previous studies also conducted in other countries that have shown that having received information from the scientific journals had a positive influence on the individual decision making regarding vaccination [29,[34][35][36][37][38][39][40][41][42]. There is clearly a need for HCWs, as part of this sample, to be able to develop competencies aimed to overall improve the vaccination uptake for them and for the general population in this geographic area.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the study conducted in Italy by Giorgia Della Polla and colleagues 21 and other studies involving a variety of methodologies and populations 21–25 and showed an increased likelihood of vaccination during the current pandemic, in our study, 59% of HCPs received an influenza vaccine in the year 2020. This rate was slightly higher as compared with the mean adherence of HCPs to influenza vaccination reported by Mereckiene et al 26 and Di Pumpo et al 27 (30% and 24.19%, respectively) and within the mean adherence range (22–83%) reported in a systematic review by Bish et al 28 but lower than expected in 2020 in the Kingdom of Saudi Arabia.…”
Section: Discussioncontrasting
confidence: 85%
“…Further suggestions on the most appropriate measures to put in place to promote HCWs influenza vaccination in the upcoming seasons may be drawn by the examination of the factors that predicted willingness to receive it. We have already mentioned the role of adherence to influenza vaccination in the previous seasons, which has been repeatedly reported in studies investigating predictors of willingness and adherence to influenza vaccination [ 21 , 27 , 28 , 29 ], demonstrating that the experience of vaccination is satisfactory for HCWs, and represents an incentive for future vaccinations. Since in Italy influenza vaccination is recommended, but not mandatory in HCWs, the positive role of adherence to previous influenza vaccination campaigns pertains to those who voluntarily underwent vaccination.…”
Section: Discussionmentioning
confidence: 70%